Left atrium structural and functional changes in arterial hypertension, and their dynamics during pharmacotherapy - B. Ya. Bart; E. A. Vartanyan; E. N. Dergunova; T. I. Skakova (Российский кардиологический журнал)
This study was conducted to investigate principal structural and functional parameters of left atrium (LA), and to evaluate the effects of combined hypotensive therapy in AH patients. Fifty-eight patients with Stage I and II AH, receving low- and moderate-dose combined therapy, as well as 30 healthy individuals, were examined. All necessary clinical diagnostic procedures, 24-hour ambulatory BP monitoring, ECG, EchoCG were perfomed at the baseline, at 3 and 6 months. Increased reserve volume (RV), LA volume and sizes, LA systolic function, and decreased LA transitory volume (TO) were observed. After 6 months of treatment, BP level, LV myocardial mass (LVMM), LA RV, LA systolic function parameters decreased significantly (p < 0.05), and LA TV increased (p < 0.05), but the latter was still lower than in the control group. Long-term antihypertensive therapy facilitated normalization of LA stucture and function, as well as left venticualr hypertrophy (LFH) regression.